RETHINKING RELIGIOUS MODERATION THROUGH THE STUDY OF INDONESIAN EXEGESIS: A STUDY OF TAFSIR AL-AZHAR BY HAMKA - Basri Basri; Muhammad Muhammad (Khazanah: Jurnal Studi Islam dan Humaniora, 2023)
Realizing religious moderation has become a medium-term program of the President for the 2020-2024 period. This program has been entrusted to the Ministry of Religious Affairs. Through a moderation team, the Ministry of Religion has formulated indicators of religious moderation, one of which is tolerance. According to the Ministry of Religion, tolerance is defined as having an open, broad-minded, voluntary, and gentle attitude towards accepting differences. Tolerance is always accompanied by respect, accepting those who are different as part of ourselves, and thinking positively. This tolerance is further divided into two categories: inter-religious and intra-religious. The hope of inter-religious tolerance is the emergence of an attitude towards followers of other religions that involves willingness to engage in dialogue, cooperation, support for the establishment of places of worship, and interacting with followers of other religions. On the other hand, Hamka is one of the prominent Muslim scholars in Indonesia known for his remarkable exegesis work that is widely studied in Asia, particularly in Indonesia. Hamka, who lived during a period of political upheaval both domestically and internationally, had a significant impact on his thinking concepts, which were later reflected in his works. This article aims to explore Hamka's views on other religions, particularly Judaism, delve deeper into the existence or absence of Jewish/Zionist conspiracies, and analyze Hamka's acceptance of other religions. The research methodology employed is literature review with a descriptive-analytic analysis as a guide in this article. The findings show that Hamka's exegesis contradicts the concept of religious moderation presented by the Ministry of Religion. In Hamka's exegesis, there are many suspicions towards Jews, although discussions on the Protocols of the Elders of Zion, according to observers, are considered conspiracies, fictional, and lack valid evidence. Additionally, Hamka falls into the category of exclusive Islam that does not accept any religion other than Muhammadanism.